Ghostly Militanz: The Loss of Discursive Infrastructures and German Antifascist Radical Counterpublics - Jones, Ali; Schuhmacher, Nils (PARTECIPAZIONE E CONFLITTO, 2024)
This article argues that German Antifa is historically grounded in radical counterpublics, established and maintained via discursive infrastructures by which activists declare, debate, justify and limit their direct actions. This process of discursive communication not only allows them to legitimize their direct action (up-to and including violence) as morally justified Militanz, but also delineates these actions as political rather than criminal. Beginning with the case study of the criminal trial against the so-called Antifa East, the paper argues that factions of German Antifa have abandoned these infrastructures, but in doing so have also lost the moral justification for their actions. By abandoning their-own movement limits and traditions, the Militanz wielded instead evokes only a ghost of that justification. Instead, these clandestine assaults – enacted without any discursive explanation or counterpublic engagement – cannot be understood as political, leaving those involved charged under the German legal code (section 129) regarding criminal rather than political and potentially terrorist (section 129a) engagement.